Legal European company forms to realize FOCJ: Functional Overlapping Competing Jurisdictions - Peter Friedrich (European Regional Science Association (ERSA), 2010)
Legal European Company Forms to Realize Cross Border FOCJ - Functional Overlapping Competing Jurisdictions Peter Friedrich Since several years Bruno Frey, Eichenberger and other authors launched the idea of a FOCJ "Functional Overlapping Competing Jurisdiction". In Switzerland and USA school jurisdictions of FOCJ-type exist. The authors mentioned expect that this form of service offering competing jurisdiction would improve the efficiency of the public sector in Europe. To contribute to this discussion one has to check whether suitable institutional legal forms are available, and one has to formulate some theory of FOCJ formation and operation. With developing European integration also cross border activities should become more efficient. This caused during the past 30 years severe difficulties as legal public cross border activities had to be based on contracts between Member States of the European Union. Meanwhile four European legal forms of company laws have been developed to promote cross border cooperation. They comprise the European Company SE, the European Economic Interest Grouping EEIG, the European Cooperative SCE, and the European Territorial Cooperation Grouping ECTG .Four others are in the legislation process. They are the European Private Company SPE, the European Mutual Society ME, The European Association EA and the European Foundation EFS. To tackle the efficiency question for cross border FOCJ we discuss which kind of FOCJ seems appropriate for which cross border activities and whether the European legal forms of companies can be applied. Moreover, we show a model for establishment of a FOCJ, the finance and operation of a FOCJ. We conclude that a European Grouping of Territorial Cooperation in the framework of a Public Private Partnership might be a promising tool to realize a cross border FOCJ.
Keywords: H1; H42; H77; R10; R58; K22; 330; Cross Border Cooperation; Functional Overlapping Competing Jurisdictions; Legal European Forms of Private or Public Law Companies; Public Private Partnership; Public-public Partnership Efficiency